Integrating motherhood and employment: A 22-year analysis investigating impacts of US workplace breastfeeding policy. (August 2020) - Hauck, Katharina; Miraldo, Marisa; Singh, Surya
Abstract: The United States has one of the lowest exclusive breastfeeding rates among high-income countries. Most experts agree that there is a lack of mother-friendly workplace policies compared to other countries. Since 1995, 25 states have implemented workplace breastfeeding legislation allowing mothers to express and store breast milk in the workplace. There is heterogeneity in policy enforceability where 17 states have weak enforceability while eight states have strict enforceability and require employers to offer provisions to breastfeed at the workplace. Using difference-in-differences methods, we examine the impact of this policy on state-level breastfeeding rates and assess how that impact differs with policy enforceability. We use data from the Centers for Disease Control on breastfeeding, supplementing with socio-economic data from the Panel Study of Income Dynamics, Current Population Survey, the US Census Bureau and several other datasets over 22 years from 1990 to 2011. We find that states with legislation experienced a 2.3-percentage point increase in breastfeeding rates compared to states without legislation while states with weak enforceability experienced a 3.1-percentage point increase compared to states without legislation. We also find that policies do not start to have an impact until 1–2 years after they were signed into law. Considering the recent assault on breastfeeding from the current administration, our study is a timely and important contribution that strengthens the evidence base for the health benefits of workplace breastfeeding policies. Highlights: Some US states have passed workplace breastfeeding policies to allow mothers to pump milk in the workplace. We assess the impact of such policies in the US on breastfeeding rates considering the heterogeneity of the policy. States with workplace breastfeeding policies experienced a 2.3-percentage point increase in breastfeeding rates. The policy impact differed by enforceability of the policy. Workplace breastfeeding policies can be an avenue to help stagnant breastfeeding rates.